Iron oxide / bismuth vanadate composite photocatalytic material as well as preparation method and application thereof in photocatalytic degradation of organic pollutants
By selectively depositing iron oxides on the {110} surface of BiVO4, forming iron oxide/bismuth vanadate composite photocatalytic material, the application restriction of BiVO4 in the field of photocatalytic pollutant degradation is solved, and more efficient Photocatalytic activity and pollutant degradation effects.
Patent Information
- Application Number
- CN202411363544.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-14
AI Technical Summary
The application of BiVO4 in the field of photocatalytic pollutant degradation is limited by the problems of fast recombination speed, insufficient stability and insufficient sunlight utilization ability.
The iron oxide/bismuth vanadate composite photocatalytic material was prepared by hydrothermal method and photodeposition method. The iron oxide formed by Fe3+ oxidation was selectively deposited on the {110} surface of bismuth vanadate to form a photocatalytic-Fenton coupling system , improve the separation rate of photogenerated carriers.
It significantly improves the photocatalytic activity, is better than the effect of pure phase BiVO4 in degrading carbamazepine, and has great application prospects in the degradation of antibiotic wastewater.
Smart Images

Figure CN119425814A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic materials, and in particular to an iron oxide / bismuth vanadate composite photocatalytic material and a preparation method thereof, and application thereof in photocatalytic degradation of organic pollutants. Background Art
[0002] Water pollution is becoming more and more serious with the intensification of human activities, and the huge risks it poses to human health have attracted widespread attention. In the face of this environmental crisis, it is urgent to find effective solutions. Photocatalytic technology, especially technology based on photocatalysts, can efficiently convert solar energy into chemical energy and is regarded as one of the most promising ways to solve environmental problems.
[0003] Among many semiconductor materials, Bi-based semiconductor materials, such as Bi2O3, BiOI, Bi2WO6, Bi2MoO6 and BiVO4, have attracted much attention due to their excellent performance. In particular, BiVO4 with a monoclinic scheelite structure has significant visible light response ability, a bandgap of 2.4 eV, and a reasonable valence band position, so it is the most widely studied and applied in the field of environmental remediation. However, BiVO4 still has some limitations in practical applications, such as fast electron-hole recombination rate, insufficient stability, and the ability to utilize sunlight needs to be improved. These problems limit its wide application in the field of photocatalytic pollutant degradation. Therefore, the development of new BiVO4-based materials with high visible light utilization, fast photogenerated carrier separation rate and low cost has become an important direction and huge challenge for current research. Summary of the invention
[0004] In order to solve or partially solve the problems existing in the related art, the present invention provides an iron oxide / bismuth vanadate composite photocatalytic material and a preparation method thereof and application in photocatalytic degradation of organic pollutants.
[0005] The present invention provides a method for preparing an iron oxide / bismuth vanadate composite photocatalytic material, which comprises the following steps: Step a), using bismuth nitrate pentahydrate and ammonium metavanadate as raw materials to prepare a bismuth vanadate precursor; Step b), using the bismuth vanadate precursor as a raw material, preparing bismuth vanadate by a hydrothermal method; Step c), using the bismuth vanadate as the substrate material, ferric chloride hexahydrate as the iron source, and potassium iodate as the electron acceptor, using a photodeposition method to obtain Fe 3+ The iron oxide formed after oxidation is selectively deposited on the {110} surface of bismuth vanadate to obtain an iron oxide / bismuth vanadate composite photocatalytic material.
[0006] Furthermore, in the step a), the mass ratio of bismuth nitrate pentahydrate to ammonium metavanadate is 0.5-1:1.
[0007] Furthermore, the step a) is specifically as follows: Dissolving bismuth nitrate pentahydrate and ammonium metavanadate in pure water to obtain bismuth nitrate solution and ammonium metavanadate solution respectively; Under magnetic stirring, the ammonium metavanadate solution is added dropwise into the bismuth nitrate solution, and the pH value is adjusted to 1.0-3.0 to obtain a bismuth vanadate precursor.
[0008] Furthermore, the step b) is specifically as follows: The bismuth vanadate precursor is subjected to a hydrothermal reaction, and the obtained precipitate is centrifuged, washed, and dried to obtain a bismuth vanadate solid; The hydrothermal reaction temperature is 180-200°C, and the hydrothermal reaction time is 12-24h.
[0009] Furthermore, the step c) is specifically as follows: Dispersing bismuth vanadate in a potassium iodate solution, and adding the obtained mixed solution to a ferric chloride hexahydrate solution to obtain a reactant; the dosage ratio of bismuth vanadate, potassium iodate and ferric chloride hexahydrate is 570-630:180-220:2.5-4; Under stirring, the reactants are irradiated with light for 2-4 hours; The mixture obtained after the light irradiation is centrifuged, washed and dried to obtain the iron oxide / bismuth vanadate composite photocatalytic material.
[0010] Furthermore, the illumination is specifically: Irradiate the reactants with a Xe lamp with a wavelength of λ ≥ 420 nm for 2-4 h at an intensity of 150-300 mW / cm 2 .
[0011] Furthermore, the rotation speed of the centrifugal separation is 5000-8000 rpm. The present invention also provides an iron oxide / bismuth vanadate composite photocatalytic material, which is prepared according to any one of the methods described above.
[0012] The present invention also provides an application of the iron oxide / bismuth vanadate composite photocatalytic material in photocatalytic degradation of organic pollutants.
[0013] Furthermore, the organic pollutant is carbamazepine.
[0014] The preparation method of the iron oxide / bismuth vanadate composite photocatalytic material provided by the present invention may have the following beneficial effects: (1) Iron oxide / bismuth vanadate composite photocatalytic material was prepared by hydrothermal method and photodeposition method. The preparation method is simple and easy to operate.
[0015] (2) The prepared iron oxide / bismuth vanadate composite photocatalytic material is a new type of binary plane selective deposition assembly. In this composite material, iron oxide is deposited on the {110} surface of bismuth vanadate, forming a photocatalytic-Fenton coupling system. Iron oxide acts as a co-catalyst to accelerate electron transfer, effectively separate electron-hole pairs, significantly increase the separation rate of photogenerated carriers, and promote the catalytic reaction.
[0016] (3) Compared with pure BiVO4, the prepared iron oxide / bismuth vanadate composite photocatalytic material has a better effect in degrading carbamazepine and has great application prospects in degrading antibiotic wastewater.
[0017] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.
[0019] Figure 1 The pure phase BiVO4 material prepared in Example 2 and the FeO prepared in Example 1 x SEM comparison of / BiVO4 composite materials; Figure 2 The BiVO4 / FeO prepared in Example 1 x XRD comparison diagram of the composite material and the pure phase BiVO4 material prepared in Example 2.
[0020] Figure 3 This is a graph showing the changes in the photodegradation concentration of carbamazepine under light conditions. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms "a", "the" and "the" used in the present invention and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0023] It should be understood that although the terms "first", "second", "third", etc. may be used to describe various information in the present invention, such information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present invention, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0024] The present invention provides a method for preparing an iron oxide / bismuth vanadate composite photocatalytic material, which is characterized by comprising the following steps: Step a), using bismuth nitrate pentahydrate and ammonium metavanadate as raw materials to prepare a bismuth vanadate precursor; Step b), using the bismuth vanadate precursor as a raw material, preparing bismuth vanadate by a hydrothermal method; Step c), using the bismuth vanadate as the substrate material, ferric chloride hexahydrate as the iron source, and potassium iodate as the electron acceptor, using a photodeposition method to obtain Fe 3+ The iron oxide formed after oxidation is selectively deposited on the {110} surface of bismuth vanadate to obtain an iron oxide / bismuth vanadate composite photocatalytic material.
[0025] To simplify the description, the above iron oxide can be abbreviated as FeO x , x is 1~2. The prepared iron oxide / bismuth vanadate composite photocatalytic material can also be abbreviated as FeO x / BiVO4 composite photocatalytic materials.
[0026] The performance and application of a single semiconductor material are greatly limited and cannot meet the application requirements in the actual process. The inventors of this application first considered adding a co-catalyst to effectively improve the photocatalytic efficiency of the photocatalyst. There are two main types of co-catalysts: reduction promoters and oxidation promoters. In general, noble metals transfer electrons and can be used as efficient proton reduction promoters, such as Au, Ag, Pt, Pd, etc. Some metal oxides that are homologous to artificial photosynthesis catalysts can be used as oxidation promoters, such as Fe2O3, RuO2, MnO x, IrO2, etc. Furthermore, the photocatalytic performance of BiVO4 is related to its structure. The main exposed surfaces at different positions of the decahedral BiVO4 correspond to the {010} plane and the {110} plane, respectively, and the photogenerated carriers preferentially dissociate and aggregate on the {010} plane and the {110} plane. Therefore, effective charge separation is achieved due to the driving strength generated by the different energies of the conduction band and the valence band of the two facets. In order to better improve the photocatalytic activity of BiVO4, the present application finally selects iron oxide as an oxidation co-catalyst to be deposited on the {110} plane of BiVO4. Iron oxide not only has good oxidation performance to provide a superior synergistic effect, but also its energy band energy level structure can be well matched with BiVO4 to improve the photocatalytic performance by adding co-catalysts. Photogenerated electrons and holes can be further transferred to these co-catalysts for surface catalytic reactions.
[0027] In the above preparation method, step a) is a step of preparing a bismuth vanadate precursor. In this step, the bismuth vanadate precursor prepared with bismuth nitrate pentahydrate Bi(NO3)3·5H2O and ammonium metavanadate NH4VO3 as raw materials provides reactants for the subsequent hydrothermal reaction. In this step, the mass ratio of bismuth nitrate pentahydrate to ammonium metavanadate is preferably 0.5-1:1, more preferably 0.8-1:1, and most preferably 1:1.
[0028] This step is preferably as follows: Dissolve bismuth nitrate pentahydrate and ammonium metavanadate in pure water to obtain bismuth nitrate solution and ammonium metavanadate solution respectively; add the ammonium metavanadate solution dropwise to the bismuth nitrate solution under magnetic stirring, adjust the pH value to 1.0-3.0, and obtain a bismuth vanadate precursor. More preferably, 1 M ammonia water is used to adjust the pH value, and adjusting the pH value to 2.0 is the most preferred.
[0029] Step b) is a step of preparing bismuth vanadate by hydrothermal method. In this step, the bismuth vanadate precursor prepared in step a) is used as a raw material, and the bismuth vanadate precursor is converted into a bismuth vanadate BiVO4 solid with a decahedral structure through a hydrothermal reaction. This step is preferably: The bismuth vanadate precursor is subjected to a hydrothermal reaction, for example, the bismuth vanadate precursor can be transferred to a reactor for a hydrothermal reaction; after the hydrothermal reaction, the obtained precipitate is centrifuged, washed, and dried to obtain a bismuth vanadate solid; the hydrothermal reaction temperature is preferably 180-200 ° C, and the hydrothermal reaction time is preferably 12-24h. More preferably, the hydrothermal reaction temperature is 200 ° C, and the hydrothermal reaction time is 24 h. The centrifugal speed is preferably 5000-8000 rpm.
[0030] After step b), a bismuth vanadate solid with a decahedral structure is obtained, which is used as the matrix material of the composite material. Then, the iron oxide / bismuth vanadate composite photocatalytic material can be prepared according to step c). The composite material is synthesized by photodeposition technology, with bismuth vanadate as the base material, ferric chloride hexahydrate as the iron source, and potassium iodate as the electron acceptor. During the photodeposition process, light energy excites BiVO4 to generate photogenerated electrons and holes, and the photogenerated holes gather on the {110} surface and react with Fe 3+ Oxidation-reduction reaction occurs to form FeO x At the same time, KIO3 acts as an electron acceptor to capture photogenerated electrons, maintain charge balance, and promote the separation of photogenerated carriers.
[0031] The above step c) may specifically be: Dispersing bismuth vanadate in a potassium iodate solution, and adding the obtained mixed solution to a ferric chloride hexahydrate solution to obtain a reactant; the dosage ratio of bismuth vanadate, potassium iodate and ferric chloride hexahydrate is preferably 570-630:180-220:2.5-4, and more preferably 600:200:3; Under stirring, irradiate the reactants with light for 2-4 hours; The mixture obtained after the light irradiation is centrifuged, washed and dried to obtain the iron oxide / bismuth vanadate composite photocatalytic material.
[0032] The concentration of bismuth vanadate in the mixed solution is preferably 6 mg / L, and the concentration of potassium iodate is preferably 10 mM. The illumination is specifically: using a Xe lamp with λ≥ 420 nm to irradiate the reactants for 2-4 h, with an illumination intensity of 150-300 mW / cm 2 The rotation speed of centrifuging the mixture obtained after irradiation is preferably 5000-8000 rpm, washing is preferably performed with ethanol, and the drying temperature is preferably 40-60°C.
[0033] The method for preparing the iron oxide / bismuth vanadate composite photocatalytic material provided by the embodiment of the present invention has the following advantages: (1) Iron oxide / bismuth vanadate composite photocatalytic material was prepared by hydrothermal method and photodeposition method. The preparation method is simple and easy to operate.
[0034] (2) The prepared iron oxide / bismuth vanadate composite photocatalytic material is a new type of binary plane selective deposition assembly. In this composite material, FeO x Deposited on the {110} surface of bismuth vanadate, a photocatalytic-Fenton coupling system is formed. FeOx acts as a co-catalyst to accelerate electron transfer, effectively separate electron-hole pairs, significantly increase the separation rate of photogenerated carriers, and promote the catalytic reaction. The composite material has a suitable bandgap and good charge separation performance, which effectively improves the photocatalytic activity.
[0035] (3) Compared with pure BiVO4, the prepared iron oxide / bismuth vanadate composite photocatalytic material has a better effect in degrading carbamazepine and has great application prospects in degrading antibiotic wastewater.
[0036] Another embodiment of the present invention further provides an iron oxide / bismuth vanadate composite photocatalytic material, which is prepared by the method of the above embodiment. The specific implementation method and beneficial effects are the same as those of the above embodiment, and this embodiment will not be repeated here.
[0037] Another embodiment of the present invention further provides an application of the above iron oxide / bismuth vanadate composite photocatalytic material in photocatalytic degradation of organic pollutants. The organic pollutant is preferably carbamazepine.
[0038] The technical scheme of the present invention is further described below in conjunction with specific examples. The reagents used in the following examples, ethanol, ammonia water, ammonium metavanadate, bismuth nitrate pentahydrate, carbamazepine, and ferric chloride hexahydrate were purchased from Shanghai Aladdin Reagent Co., Ltd.
[0039] Example 1 Preparation of FeO x / BiVO4 composite materials 3.5 mmol ammonium metavanadate was dissolved in 20 mL 1 mol / L nitric acid solution to prepare mixed solution A, 3.5 mmol bismuth nitrate pentahydrate was dissolved in 20 mL 1 mol / L nitric acid solution to prepare mixed solution B, solution B was added dropwise to solution A under magnetic stirring, pH = 2.0 was adjusted with 1 mol / L ammonia solution to obtain BiVO4 precursor. The mixed solution containing BiVO4 precursor was transferred to a reactor for hydrothermal reaction at 200℃ for 24 h, and the obtained solid was centrifuged (speed was 7000 rpm), washed, and dried to obtain BiVO4; 0.3 g BiVO4 powder was dispersed into 50 mL 0.01M KIO3 solution. Then, 3.0 mL 0.5 g / LFeCl3 was added. . 6H2O solution. Under continuous stirring, the mixture was irradiated with a PL-XQ500W Xe lamp (λ≥420 nm) for 3 h, and the obtained mixed solution was centrifuged (rotation speed was 7000 rpm), then washed with ethanol 3 times and dried at 60 °C to obtain FeO x / BiVO4 composite materials.
[0040] Example 2 Preparation of pure phase BiVO4 material The BiVO4 precursor prepared in Example 1 was directly placed in a reactor and calcined at 200°C for 24 h, then centrifuged and washed, and dried to obtain a pure phase BiVO4 material.
[0041] Figure 1 The pure phase BiVO4 material prepared in Example 2 and the FeO prepared in Example 1 x SEM comparison of / BiVO4 composite materials; in the figure: a is pure phase BiVO4 material, b is FeO x / BiVO4 composite materials; Figure 1 It can be seen that the pure phase BiVO4 material is a block structure with a smooth surface; x / BiVO4 composites have a rough surface due to the massive FeO x The {110} surface of BiVO4 becomes rough, while the {010} surface remains smooth, indicating that FeO x Selectively deposits only on {110} planes.
[0042] Figure 2 The BiVO4 / FeO prepared in Example 1 x XRD comparison diagram of the composite material and the pure phase BiVO4 material prepared in Example 2. Figure 2 It can be found that the characteristic diffraction peaks of pure phase BiVO4 material completely correspond to the standard card BiVO4 (PDF#75-1867) and there are no impurity peaks. x The characteristic diffraction peaks of the composite material completely match the diffraction peaks of the pure phase BiVO4 material, and the positions of the diffraction peaks do not shift, indicating that FeO x The deposition has no effect on the crystal form of BiVO4.
[0043] The photocatalytic activities of the photocatalysts prepared in Example 1 and Example 2 were evaluated.
[0044] The evaluation method is as follows: Using a 300W xenon lamp to irradiate, 40 mL of carbamazepine simulated wastewater was added to the reactor and its initial value was determined. Then, 20 mg of the prepared catalyst and 72 μL of hydrogen peroxide (H2O2) were added. Magnetic stirring was used to keep the catalyst in a suspended or floating state. Then, 2 mL of samples were taken at intervals during the illumination process for analysis. Degradation rate formula: n=[(1-Ct / Co)]x100%, where C0 is the initial value of the pollutant, C t The concentration of the solution measured by regular sampling.
[0045] Evaluation results: Please see Figure 3 , FeO prepared in Example 1 xThe degradation rate of carbamazepine by the FeO / BiVO4 composite material reached 100% within 20 min. The degradation rate of carbamazepine by the pure phase BiVO4 material prepared in Example 2 reached 30% within 20 min. x The degradation rate of / BiVO4 composite materials is significantly improved, and the catalytic performance is excellent.
[0046] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing an iron oxide / bismuth vanadate composite photocatalytic material, characterized in that: The steps include: Step a), using bismuth nitrate pentahydrate and ammonium metavanadate as raw materials to prepare a bismuth vanadate precursor; Step b), using the bismuth vanadate precursor as a raw material, preparing bismuth vanadate by a hydrothermal method; Step c), using the bismuth vanadate as the substrate material, ferric chloride hexahydrate as the iron source, and potassium iodate as the electron acceptor, using a photodeposition method to obtain Fe 3+ The iron oxide formed after oxidation is selectively deposited on the {110} surface of bismuth vanadate to obtain an iron oxide / bismuth vanadate composite photocatalytic material.
2. The preparation method according to claim 1, characterized in that: In the step a), the mass ratio of bismuth nitrate pentahydrate to ammonium metavanadate is 0.5-1:
1.
3. The preparation method according to claim 2, characterized in that: The step a) is specifically as follows: Dissolving bismuth nitrate pentahydrate and ammonium metavanadate in pure water to obtain bismuth nitrate solution and ammonium metavanadate solution respectively; Under magnetic stirring, the ammonium metavanadate solution is added dropwise into the bismuth nitrate solution, and the pH value is adjusted to 1.0-3.0 to obtain a bismuth vanadate precursor.
4. The preparation method according to claim 1, characterized in that: The step b) is specifically as follows: The bismuth vanadate precursor is subjected to a hydrothermal reaction, and the obtained precipitate is centrifuged, washed, and dried to obtain a bismuth vanadate solid; The hydrothermal reaction temperature is 180-200°C, and the hydrothermal reaction time is 12-24h.
5. The preparation method according to claim 1, characterized in that: The step c) is specifically as follows: Dispersing bismuth vanadate in a potassium iodate solution, and adding the obtained mixed solution to a ferric chloride hexahydrate solution to obtain a reactant; the dosage ratio of bismuth vanadate, potassium iodate and ferric chloride hexahydrate is 570-630:180-220:2.5-4; Under stirring, the reactants are irradiated with light for 2-4 hours; The mixture obtained after the light irradiation is centrifuged, washed and dried to obtain the iron oxide / bismuth vanadate composite photocatalytic material.
6. The preparation method according to claim 5, characterized in that: The illumination is specifically: Irradiate the reactants with a Xe lamp with a wavelength of λ ≥ 420 nm for 2-4 h at an intensity of 150-300 mW / cm 2 .
7. The preparation method according to claim 4 or 5, characterized in that: The rotation speed of the centrifugal separation is 5000-8000 rpm.
8. An iron oxide / bismuth vanadate composite photocatalytic material, characterized in that: It is prepared according to the method according to any one of claims 1 to 7.
9. Use of the iron oxide / bismuth vanadate composite photocatalytic material according to claim 8 in photocatalytic degradation of organic pollutants.
10. The use according to claim 9, characterized in that: The organic pollutant is carbamazepine.
Citation Information
Patent Citations
Fe2O3-coated BiVO4 photocatalytic material as well as preparation method and application thereof
CN117181233A
Method for preparing Fe2O3 / BiVO4 heterojunction through photoselective deposition and application of Fe2O3 / BiVO4 heterojunction in photocatalytic degradation of antibiotics
CN117839711A
Cited By
Thiocyanide-modified Ag / BiVO4 and application of thiocyanide-modified Ag / BiVO4 in preparation of aminomethyl phosphoric acid through photocatalytic oxidation of glyphosate
CN120132918A